2019
DOI: 10.3389/fpsyg.2019.02524
|View full text |Cite
|
Sign up to set email alerts
|

Körperkoordinationstest Für Kinder (KTK) for Brazilian Children and Adolescents: Factor Analysis, Invariance and Factor Score

Abstract: The decrease in children motor competence, with a consequent reduction in the levels of physical activities and fitness, impacting health negatively, has affected children across countries. In addition to consistent intervention strategies, it is necessary to use appropriate instruments. The Körperkoordinationstest Für Kinder (KTK) is a reliable and low-cost motor coordination (MC) test used in several countries but lacking psychometric evidence in the Brazilian population. The present study investigates the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
2
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 23 publications
0
26
2
6
Order By: Relevance
“…Three studies evaluated the validity and reliability of the Körperkoordinationstest für Kinder (KTK) [ 77 , 80 , 136 ]. Two studies looked at the structural validity of the KTK, and found adequate evidence to support a one factor structure, interpreted as representing “body coordination” [ 77 , 80 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies evaluated the validity and reliability of the Körperkoordinationstest für Kinder (KTK) [ 77 , 80 , 136 ]. Two studies looked at the structural validity of the KTK, and found adequate evidence to support a one factor structure, interpreted as representing “body coordination” [ 77 , 80 ].…”
Section: Resultsmentioning
confidence: 99%
“…Three studies evaluated the validity and reliability of the Körperkoordinationstest für Kinder (KTK) [ 77 , 80 , 136 ]. Two studies looked at the structural validity of the KTK, and found adequate evidence to support a one factor structure, interpreted as representing “body coordination” [ 77 , 80 ]. The internal consistency of the KTK was consistently found to be good across samples in Finland, Portugal and Belgium (α ranged from .78 - .83), however, as hypothesised there were significant differences between groups, in which children from Portugal and Belgium performed worse than Finnish participants [ 136 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ao comparar com o estudo de Moreira et al 10 , é possível afi rmar que o presente estudo converge com os achados dos autores supracitados, porém, alguns critérios psicométricos foram melhores do que os observados por eles, especifi camente, em relação ao χ 2 /gl e, em especial, ao Pclose, o qual não encontrado no estudo citado. Este indicador é uma ponderação do teste de hipótese nula do RMSEA, o qual, sugere sua rejeição ou não, quando esse valor for próximo de zero, recomendando ser > 0.05, condição que garante a qualidade e parcimônia dos ajustes no modelo da estrutura hipotetizada.…”
Section: Discussionunclassified
“…Com objetivo de avaliar a estrutura fatorial do KTK na referida amostra, além dos cálculos supracitados, realizou-se uma análise fatorial confi rmatória no programa estatístico AMOS 21.0. Neste, pretendeu-se avaliar a consistência da estrutura fatorial do modelo do KTK, previamente proposta por Kiphard e Schilling 10 . Sendo assim, considerou-se como entrada, a matriz de covariância, tendo sido adotado o estimador ML (Maximum-Likelihood).…”
Section: Preparação E Análise Dos Dadosunclassified
See 1 more Smart Citation